Lens thickness and associated ocular biometric factors among cataract patients in tertiary hospital - Shivani Sharma; Anil Kumar Sharma; Satish Gupta; Divyanshi Gupta (International Journal of Research in Medical Sciences, 2023)
Background: A significant factor in determining intraocular lens power is the biometry assessment of cataract patients prior to surgery. To evaluate the distribution of lens thickness (LT) and its associations with other ocular biometric factors among cataract patients. Methods: Total 978 eyes from cataract patients were retrospectively included. Ocular biometric factors including k1, k2, LT, central corneal thickness (CCT), anterior chamber depth (ACD), white-to-white (WTW) distance, and axial length (AL) were collected based on the medical records. The associations between LT and general or ocular factors were assessed. We analyzed the data using descriptive analysis and correlated each variable using the Spearman’s Rho analysis. Results: The mean age was 62.5±15.70 years and 55.11% were females. Mean LT was 4.35±0.41 mm. The LT was greater in older patients. LT positively correlated with AL, WTW and CCT, while negatively correlated with ACD. Conclusions: LT is an important biometric parameter that should be considered, along with other biometric parameters, in determining effective lens position in patients undergoing cataract surgery. ACD is predominantly influenced by LT than the AL.